Strategy Development of PT XYZ A Startup Technology Company (The Indonesian Journal of Business Administration, 2012)
PT. XYZ (XYZ) is an Indonesian startup technology company which provides IT Consulting and System Integration services. In this research, XYZâ€™s strategy for the next three years (until 2015) will be crafted by going through the strategic management process which consists of the following stages: (1) environment analysis of XYZ, (2) setting strategic vision, (3) setting objective, (4) crafting strategy and (5) executing the strategy. Based on the result of the environment analysis, XYZâ€™s vision, its objective and its strategy are determined and discussed. In a nut shell, XYZâ€™s strategy is to â€œreach IDR 50 Billion revenues in 2015 with 15-20% net margin by offering innovative technology solutions to support customerâ€™s operations and supply management through prestigious projects which deliver superior requirement analysis, high value and reliable support.â€Â This strategy is supported by a well thought diamond model strategy elaboration and its corresponding activity system map, value chain and business model. This research also provides implementation plan for XYZ as the basis for executing the strategy. Â Keywords: company strategy, strategic management, startup technology company